Hubungan Rasio Albumin Kreatinin Urin dengan Frekuensi Hemodialisis pada Gagal Ginjal Kronis - Chindi Y. Tomayahu; Astika Nur Rohmah; Suryanto (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Chronic kidney disease (CKD) is a global public health issue, with its prevalence increasing annually. CKD involves a pathophysiological process with diverse etiologies, such as uncontrolled diabetes, uncontrolled hypertension, or chronic glomerulonephritis, which lead to progressive kidney function decline, requiring patients to undergo routine hemodialysis. This study aims to determine the relationship between the Albumin- Creatinine Ratio (ACR) and the frequency of hemodialysis in patients with chronic kidney disease. This research employs a systematic review method, collecting data from various research journals available on Google Scholar and PubMed. The results indicate that CKD patients were predominantly male and were most vulnerable between the ages of 40-59 years. Hemodialysis was typically performed 2-3 times per week. The longer the duration of hemodialysis treatment, the more significant its impact on the albumin and creatinine ratio. While the albumin-creatinine ratio can be used to identify early kidney disease, its relationship with albumin and creatinine examination parameters was weak The albumin-creatinine ratio (ACR) test can serve as an early diagnostic support for chronic kidney disease. Further research is needed on the quality of life of CKD patients based on the duration of hemodialysis. Additionally, there should be increased awareness among CKD patients about their dietary patterns, particularly protein intake.